Determinants Of Economic Growth In 6 Asean Countries From 2018 To 2022 - Sholati, Saharani Neitha; Setyowati, Eni; Hasmarin, Maulidyah Indira (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
This study aims to investigate the factors influencing economic growth in Southeast Asia, focusing on government expenditure, the Human Development Index (HDI), foreign direct investment (FDI), labor, and international tourism expenditure on Gross Domestic Product (GDP) in six Southeast Asian countries (Indonesia, Singapore, Thailand, Malaysia, Vietnam, and the Philippines) during the 2014–2021 period. Economic growth in this region is influenced by various external and internal factors that need to be examined more deeply. The method used is panel data regression with the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM) approaches. The estimation results indicate that the FEM model is the most appropriate, with a coefficient of determination (R²) of 0.9993, meaning that 99.93% of GDP variation can be explained by these variables. Government expenditure and FDI have a significant effect on GDP, while HDI, labor, and international tourism expenditure do not show a significant effect. These findings align with previous studies suggesting that government expenditure and FDI are the main factors influencing economic growth, while the impact of other factors is more limited.